Perspectives of Health Promotion – A Personal View - Schelp, Frank P. (วารสารวิจัยสาธารณสุขศาสตร์ มหาวิทยาลัยขอนแก่น, 2017)
Since some time by now the health delivery system of Thailand has to deal with an increase of so called ‘chronic’ diseases. I addition, to improve accessibility of the overall population to the health service, a number of innovative health security schemes had been introduced. Preventive measures are required for finally reducing the costs of treatment for the ever increasing numbers of patients with ‘chronic diseases’. It is well accepted from health professionals that major reasons for acquiring ‘chronic diseases’ are linked to the behavioral pattern of the people, but behavioral attitudes however are difficult to change. There are remarkable differences in the way to cope with the complex interchange between the occurrence of chronic diseases, attempts to control them and to consider how to cover the cost for the health delivery system when comparing a country, known for an extensive social security system since more than 100 years and Thailand. The pros and cons of both ways are reflected in a very personal way in this contribution.